Natural products for migraine: Data-mining analyses of Chinese Medicine classical literature - Zhang, Claire Shuiqing; Lyu, Shaohua; Zhang, Anthony Lin; Guo, Xinfeng; Sun, Jingbo; Lu, Chuanjian; Luo, Xiaodong; Xue, Charlie Changli (Frontiers in Pharmacology, 2022)
Background: Treatment effect of current pharmacotherapies for migraine is unsatisfying. Discovering new anti-migraine natural products and nutraceuticals from large collections of Chinese medicine classical literature may assist to address this gap. Methods: We conducted a comprehensive search in the Encyclopedia of Traditional Chinese Medicine (version 5.0) to obtain migraine-related citations, then screened and scored these citations to identify clinical management of migraine using oral herbal medicine in history. Information of formulae, herbs and symptoms were further extracted. After standardisation, these data were analysed using frequency analysis and the Apriori algorithm. Anti-migraine effects and mechanisms of actions of the main herbs and formula were summarised. Results: Among 614 eligible citations, the most frequently used formula was chuan xiong cha tiao san (CXCTS), and the most frequently used herb was chuan xiong. Dietary medicinal herbs including gan cao, bai zhi, bo he, tian ma and sheng jiang were identified. Strong associations were constructed among the herb ingredients of CXCTS formula. Symptoms of chronic duration and unilateral headache were closely related with herbs of chuan xiong, gan cao, fang feng, qiang huo and cha. Symptoms of vomiting and nausea were specifically related to herbs of sheng jiang and ban xia. Conclusion: The herb ingredients of CXCTS which presented anti-migraine effects with reliable evidence of anti-migraine actions can be selected as potential drug discovery candidates, while dietary medicinal herbs including sheng jiang, bo he, cha, bai zhi, tian ma, and gan cao can be further explored as nutraceuticals for migraine.